2009
DOI: 10.1001/archophthalmol.2009.39
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Phacoemulsification Energy on the Redox State of Cultured Human Corneal Endothelial Cells

Abstract: To evaluate the effects of phacoemulsification energy on the redox state and mitochondrial distribution of cultured human endothelial cells. Methods: Human corneal endothelial cells from fresh banked human donor tissue not suitable for transplantation were harvested and cultured. Cellular autofluorescence images were obtained using an inverted microscope. The redox fluorometric ratio, which can be related to oxidative stress, was calculated as the net value of fluorescence from the 4,6-diamidino-2-phenylindole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 32 publications
1
21
0
7
Order By: Relevance
“…52 Laboratory and animal studies have shown that ultrasound power within the anterior chamber causes oxidative stress and cellular injury, with the production of free radicals that are toxic to the corneal endothelium. 53,54 However, the magnitude of this cellular damage in vivo with modern phacoemulsification techniques is uncertain, so its clinical relevance remains unclear.…”
Section: Lens Liquefaction and Fragmentationmentioning
confidence: 99%
“…52 Laboratory and animal studies have shown that ultrasound power within the anterior chamber causes oxidative stress and cellular injury, with the production of free radicals that are toxic to the corneal endothelium. 53,54 However, the magnitude of this cellular damage in vivo with modern phacoemulsification techniques is uncertain, so its clinical relevance remains unclear.…”
Section: Lens Liquefaction and Fragmentationmentioning
confidence: 99%
“…Lens pretreatment with these functions offers significant advantage compared with manual surgery. Additionally, laboratory and animal studies have shown that ultrasound power within the anterior chamber causes oxidative stress and cellular injury and production of free radicals, which can damage the corneal endothelium [20,21]. 7), sextants (Fig.…”
Section: Key Pointsmentioning
confidence: 99%
“…Ultrasound energy introduced by conventional phacoemulsification may damage surrounding structures, resulting in endothelial cell loss [19, 20]. Therefore, a reduction in ultrasound phacoemulsification may markedly reduce postoperative corneal endothelial cell loss [21, 22]. In this study, FLACS was not superior to CPCS on postoperative corneal endothelial cell loss (MD = 197.82, 95% CI: 2.66~392.97, P = 0.05).…”
Section: Discussionmentioning
confidence: 72%